Implementasi Nilai-Nilai Kejujuran Dan Kedisiplinan Dalam Pembelajaran Pendidikan Agama Islam Di Perguruan Tinggi Umum: Studi Kasus Pembentukan Karakter Mahasiswa - Nurhilaliyah (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study explores the strategies and dynamics of implementing the values of honesty and discipline through Islamic Religious Education (PAI) courses in Public Universities (PTU). Amid the ongoing issues of moral degradation and academic ethical challenges, PTUs carry a strategic responsibility not only to produce intellectually competent professionals but also individuals with integrity. This research employs a qualitative approach using a case study method at State University [Pseudonym]. Data were collected through in-depth interviews with PAI lecturers and students, participatory observation during the learning process, and analysis of Semester Learning Plan (RPS) documents. The findings indicate that: (1) Value internalization is carried out through the integration of the hidden curriculum and lecturer role modeling; (2) Problem-based learning methods are effective in stimulating academic honesty; and (3) The main challenges include the dichotomy between general and religious sciences and a heterogeneous social environment. The study concludes that PAI in PTU must transform from merely transferring cognitive knowledge into a holistic character-building platform.